Encoding of contextual fear memory in hippocampal–amygdala circuit - Kim, Woong Bin; Cho, Jun-Hyeong (Nature communications, 2020)
In contextual fear conditioning, experimental subjects learn to associate a neutral context with an aversive stimulus and display fear responses to a context that predicts danger. Although the hippocampal–amygdala pathway has been implicated in the retrieval of contextual fear memory, the mechanism by which fear memory is encoded in this circuit has not been investigated. Here, we show that activity in the ventral CA1 (vCA1) hippocampal projections to the basal amygdala (BA), paired with aversive stimuli, contributes to encoding conditioned fear memory. Contextual fear conditioning induced selective strengthening of a subset of vCA1–BA synapses, which was prevented under anisomycin-induced retrograde amnesia. Moreover, a subpopulation of BA neurons receives stronger monosynaptic inputs from context-responding vCA1 neurons, whose activity was required for contextual fear learning and synaptic potentiation in the vCA1–BA pathway. Our study suggests that synaptic strengthening of vCA1 inputs conveying contextual information to a subset of BA neurons contributes to encoding adaptive fear memory for the threat-predictive context. Previous studies implicate the hippocampal–amygdala pathway in contextual fear conditioning, in which animals learn to associate a neutral context with an aversive stimulus and display fear responses to dangerous situations. Here the authors show that selective strengthening of hippocampal–amygdala pathway contributes to encoding adaptive fear memory for threat-predictive context.